KORELASI MOTIVASI BELAJAR PAI TERHADAP KEMANDIRIAN BELAJAR DI SMP NEGERI 36 BANDAR LAMPUNG - Idri Utama, Muhammad; Hijriyah, Umi; Hasanah, Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the relationship between learning motivation in Islamic Religious Education (IRE) and the learning autonomy of eighth-grade students at SMP Negeri 36 Bandar Lampung using a quantitative correlational approach. The population comprised 240 students, from which 71 students were selected through simple random sampling. Data were collected using validated and reliable questionnaires measuring learning motivation and learning autonomy, and analyzed using the Pearson Product–Moment correlation technique. The results reveal that learning motivation in IRE does not have a significant relationship with students’ learning autonomy; although the relationship is positive, the correlation is very weak, with learning motivation accounting for only 4.6% of the variance in learning autonomy. This finding indicates that increases in learning motivation are not necessarily followed by corresponding improvements in students’ independent learning abilities. The novelty of this study lies in its focus on the relationship between learning motivation and learning autonomy in IRE within the context of post-pandemic face-to-face instruction at the junior secondary school level, a setting that remains underexplored in existing literature, while also emphasizing the religious dimension as a potential source of intrinsic motivation. The implications suggest that strengthening learning autonomy cannot rely solely on enhancing learning motivation but requires a more comprehensive approach that integrates effective instructional strategies, classroom management, and the systematic cultivation of independent learning habits. These findings contribute to the advancement of educational scholarship, particularly in the development of contextual, adaptive, and student-centered IRE learning models.